2020
DOI: 10.2147/clep.s229056
|View full text |Cite
|
Sign up to set email alerts
|

<p>Caesarean Delivery and Risk of Chronic Inflammatory Diseases (Inflammatory Bowel Disease, Rheumatoid Arthritis, Coeliac Disease, and Diabetes Mellitus): A Population Based Registry Study of 2,699,479 Births in Denmark During 1973–2016</p>

Abstract: Background: Chronic inflammatory diseases in childhood and early adult life share aetiological factors operating from birth and onwards. In this study, we use data from the national Danish health registers to evaluate the risk of developing four common, immune-mediated hospital-diagnosed childhood chronic inflammatory diseases. Methods: A national population-based registry study. Data from the Danish Medical Birth Registry and the Danish National Patient Registry from January 1973 to March 2016 were linked at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 39 publications
1
37
1
2
Order By: Relevance
“… 47 , 48 A study of a Danish register-based cohort reported CS babies to have increased susceptibility for chronic inflammatory diseases including diabetes, arthritis, inflammatory bowel disease, and celiac disease. 49 However, another study found no link between delivery mode and risk for celiac disease. 50 Numerous factors accompanying birth may complicate interpretation of such studies, including the use of antibiotics, dominant mode of newborn nutrition immediately after birth and maternal stress and health.…”
Section: Perinatal Microbial Encountersmentioning
confidence: 99%
“… 47 , 48 A study of a Danish register-based cohort reported CS babies to have increased susceptibility for chronic inflammatory diseases including diabetes, arthritis, inflammatory bowel disease, and celiac disease. 49 However, another study found no link between delivery mode and risk for celiac disease. 50 Numerous factors accompanying birth may complicate interpretation of such studies, including the use of antibiotics, dominant mode of newborn nutrition immediately after birth and maternal stress and health.…”
Section: Perinatal Microbial Encountersmentioning
confidence: 99%
“…The strengths and weaknesses of this cohort have been discussed previously. 15 The main strength of this observational study is the inclusion of more than 2.5 million nationwide births with complete ascertainment. The most common CIDs among children treated at hospitals in Denmark were chosen with an overall rate of CID among the parents of 8.4–9.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In a very interesting proof of concept study, Korpela and co-authors [ 70 ] showed the potential beneficial effects of maternal fecal transplant (MFT) on the gut microbial development of infants born by cesarean section (CS). Interestingly, they showed that the intestinal microbiota of CS children seems to be associated with a potential increased risk of developing inflammatory diseases [ 71 ]. The application of MFT to CS-born infants was shown to restore a microbiome development very similar to what is observed in vaginally born infants.…”
Section: Limitations and Functional Perspectivesmentioning
confidence: 99%